Prisoner Society in an Era of Psychoactive Substances, Organized Crime, New Drug Markets and Austerity - Gooch, Kate (The British journal of criminology, 2020)
Framed by the limited and now dated ethnographic research on the prison drug economy, this article offers new theoretical and empirical insights into how drugs challenge the social order in prisons in England and Wales. It draws on significant original and rigorous ethnographic research to argue that the ‘era of hard drugs’ has been superseded by an ‘era of new psychoactive drugs’, redefining social relations, transforming the prison illicit economy, producing new forms of prison victimization and generating far greater economic power and status for suppliers. These changes represent the complex interplay and compounding effects of broader shifts in political economy, technological advances, organized crime, prison governance and the declining legitimacy and moral performance of English and Welsh prisons.